Aerosol optical characteristics and radiative forcing in urban Beijing. (1st September 2019) - Zhao, Shuman; Hu, Bo; Du, Chaojie; Tang, Liqin; Ma, Yongjing; Liu, Hui; Zou, Jianan; Liu, Zirui; Wei, Jie; Wang, Yuesi
Abstract: Atmospheric aerosol particles exert significant influence on the earth's radiation budget, and accurate measurement of aerosol optical properties can help reduce the uncertainties in estimating aerosol radiative forcing. Therefore, year-round measurements of aerosol optical properties from August 2016 to July 2017 at an urban site in Beijing were analysed. The results show that the annual mean scattering coefficient (σsp at 550 nm, 131 ± 135 Mm −1 ) was approximately half of the measurement in Beijing from 2008 to 2009 and from 2005 to 2006, mainly due to the reduction of PM2.5 and scattering aerosols in recent years. Meanwhile, annual mean of σabs (637 nm) and SSA was 14 ± 11 Mm −1 and 0.85 ± 0.06, respectively. Seasonally, σsp during winter was approximately two times higher than in other seasons, while σabs was higher during autumn and winter, which may be attributed to biomass and fossil fuel burning under a shallow and stable boundary layer. Diurnal variation of σsp showed an evening peak and a slight morning peak in spring and summer, as well as a night peak in autumn and winter. σabs in four seasons were basically unimodal, with a morning peak in spring and summer, and a night peak in autumn and winter. In addition, the scattering Ångström exponent and backscattering Ångström exponent suggested the dominance of micro-size aerosols. Seasonal variations of SAE, BAE and the backscatter fraction indicated a larger proportion of isotropic scattering and fine-mode particles in summer and autumn, as well as a dominance of coarse particles in spring and a complicated aerosol type distribution and emission sources in winter. Furthermore, radiative forcing was estimated by a radiative transfer model. Radiative forcing varied between −6.69 and −235.67 Wm -2 (with the average of −54.93 ± 39.92 Wm -2 ) at the surface, with a mean of 35.56 ± 22.88 Wm -2 in the atmosphere. Graphical abstract: Image 1 Highlights: Year-round aerosol optical characteristics in Beijing are observed and analysed. Seasonal and diurnal variation and the causes are discussed. Changes are discovered compared with earlier years in Beijing and other regions. Estimate the aerosols radiative forcing in Beijing.